Proposal for a lighting design laboratory. An online teaching experience (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
This article seeks, through an experience that I had as a professor at the   university of Évora, Portugal, thinking, dialoguing with pedagogical alternatives that start from what Andrea DiSessa calls “intuitive knowledge”, the possibility of building a scenic lighting design laboratory based on the use of technological tools as the camera and the three-dimensional lighting simulator. Such laboratory allows the study of lighting design narrative processes even in enviroments in wich is not possible to share space between parts, but it's use can also be combined with daily practical experiences, making it a usefull tool in any kind of creative process with light.